Paramedics’ Experiences of Structured Documentation in the Finnish KEJO Electronic Patient Care Record: A Qualitative Survey Study - Hihnala, Jaakko; Sivula, Niko; Roivainen, Petri; Salminen-Tuomaala, Mari (European Journal of Applied Sciences, 2026)
Structured documentation in electronic patient care records is intended to improve the consistency, retrievability and continuity of clinical information. In emergency medical services, however, documentation is performed in mobile, time-critical and clinically complex environments, which places specific demands on system usability and workflow compatibility. This study describes paramedics’ experiences of structured documentation in the KEJO electronic patient care record, the national electronic patient care record used in Finnish emergency medical services. The study was conducted as a cross-sectional survey with a qualitative emphasis. Data were collected in spring 2024 using an anonymous Webropol questionnaire distributed to paramedics working in operational field duties within Oulu University Hospital Emergency Medical Services in Finland. A total of 137 paramedics responded. This article focuses on open-ended responses, which were analysed using inductive content analysis. The findings show that structured documentation in the KEJO electronic patient care record was experienced as challenging particularly because of usability problems, fragmented documentation views, technical slowness and limitations in structured data fields. Respondents described the documentation process as slow, illogical and insufficiently flexible for prehospital care. These challenges were perceived to increase workload, reduce the clarity of documented information and make it more difficult to record clinically relevant details. Shortcomings were also identified in the timing, content and practical implementation of user training. The findings suggest that the further development of the KEJO electronic patient care record should prioritise user-centred design, workflow compatibility, technical reliability and case-based training to better support information continuity, paramedic workflow and patient safety.